Understanding the links between agriculture and health: Agriculture and health in the policymaking process - Benson, Todd (International Food Policy Research Institute, 2006)
Earlier briefs in this series make the case that there is added value for the agricultural and health sectors in working more closely together to address problems of human well-being that fall at the intersection of the two sectors. Yet the divisions between the two sectors are wide and difficult to bridge. Building the space and providing sufficient incentives and resources for collaborative activities between them will require changes in government policy—itself not a straightforward endeavor. Moreover, the sharp human and financial resource constraints in developing countries compound the challenge. This brief describes some of the important barriers to effective collaboration between the two sectors and suggests ways to overcome them. First, though, why does policy matter in this context? Policy states how government intends to prioritize the allocation of resources under its control for what is perceived to be the best interest of society. Poor health and stagnant or declining agricultural productivity are among the most fundamental challenges to improved human welfare and economic growth. Government has the responsibility for providing many of the institutions, infrastructure, and resources — key public goods — without which many farmers, in particular, will remain unhealthy, unproductive, and mired in poverty. Thus the policies and actions of government are a critical component in enabling individuals, particularly in rural areas, to live healthier and more productive lives.